Niveles de abono orgánico en el comportamiento productivo del pasto maralfalfa (Pennisetum sp). - Tituaña Alcaciega, Robert Efraín (2012)
This research work was carried out between January and March in 2011 at the Hacienda "San Carlos", located at Km 28 via Quevedo - Santo Domingo, whose geographical coordinates are 79 ° 29 ' west longitude and 0 ° 52 'south latitude at an altitude of 120 meters. The investigation lasted 90 days. Raised the overall objective: To determine grass production using organic fertilizers maralfalfa and specific: a) Know what the treatments has the highest vegetative development, b) determine the production cost of each treatment and c) determine the best treatment bromatological composition. Subject to the assumptions: a) Treatment with an age cutoff of 75 days more concentration of manure (1500 kg / ha) will provide further development in growing vegetative maralfalfa, b) One of the treatments had a lower cost production c) Treatment with an age cutoff of 30 days more concentration of manure (1500 kg / ha) present the best bromatological composition. For the present study used a split plot design in randomized complete block, where the main plot were large or composting levels and ages of small plots court after planting. Yields of green forage biomass (kg MV ha-1), Dry forage biomass (kg MS ha-1), plant height, leaf number, leaf length and width of leaves, were significantly influenced by the ages of court increase at older ages cutting, being the age of 75 days cut that higher yields in these variables presented. The use of solid manure AGROPESA, induced a higher yield of green forage biomass, dry forage biomass, leaf number, fresh weight of stem, leaf and plant, as well as a greater length of road, compared with the control to 30, 45, 60 and 75 days. The protein content increased in the grass as they raised the level of fertilizer application, presenting the highest protein content with the use of 1500 kg ha-1 and a cutoff age of 75 days to get the 8.68%.Accordingto the results obtained in this investigation accept the first hypothesis which states that:"Treatment with an age cutoff of 75 days more concentration of manure (1500kg /ha)will provide greater vegetative grow thin culture of maralfalfa". Similarly, the second hypothesis was accepted that states: "One of the treatments presenteda lower costof production."Itrejected thethirdhypothesis, which states: "Treatment with an age cutoffof30 days more concentration of manure (1500kg /ha) present the best bromatological composition